ZERO-DEFECT ITEM MACHINING - O.A. POLUSHKIN (Advanced Engineering Research)
Original non-Gaussian distribution of item size values, derived by the qualified tool machining, might be used as a model of such a machining process. By means of this model were obtained the expressions for determination of reclaimable rejects and waste during machining. With the help of these expressions were received the sets of equations for determination of the values and tolerances of the tool setup and tool life. These values guarantee that the machining will be performed without processing defects, thus it is possible to exclude the quality control operation. Also here is proposed the computer- optimized algorithm for calculation of the mentioned above values, and a sample of its practical use.